2022
DOI: 10.1007/s00158-022-03451-2
|View full text |Cite
|
Sign up to set email alerts
|

3D shape optimization of loudspeaker cabinets for uniform directivity

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Other studies have also shown the significance of surface micropatterns, as indicated by refs. [132][133][134] These works warrant further in-depth research particularly for suspended 2D material systems.…”
Section: Electrostatic Speakers Based On 2d Materials and Their Compo...mentioning
confidence: 98%
“…Other studies have also shown the significance of surface micropatterns, as indicated by refs. [132][133][134] These works warrant further in-depth research particularly for suspended 2D material systems.…”
Section: Electrostatic Speakers Based On 2d Materials and Their Compo...mentioning
confidence: 98%
“…The frequency lines and/or angles of incident could also be included in the min-max problem, e.g. [43]. The min-max problem of Eq.…”
Section: Optimization Formulationmentioning
confidence: 99%
“…Over the past several decades, a number of numerical approaches have been proposed to calculate the design sensitivities of the static and transient responses of structural systems, compare of Reference 5 and references therein. Also, the shape and topology sensitivity analysis formulations have been presented for acoustic systems and acoustic‐structural interaction systems, 6,7 and applied to the shape optimization of noise barriers, 8 loudspeaker cabinets 9 and the distribution design of sound absorbing materials, 10 and so forth. Moreover, eigenvalue optimization problems also appear frequently when dealing with the structural stability and vibration analysis.…”
Section: Introductionmentioning
confidence: 99%